Fenomena Hidup Hedonis dalam Perspektif Al-Qur’an: Telaah Konsep Al-Isrif dan At-Tabdzir - Selmiana Salam; A Tenri Sri Muntu; Dian Sari; Nasrulah Bin Sapa (Lembaga Pengkajian Pengembangan Pendidikan dan Kewirausahaan, 2025)
Hedonistic lifestyles characterized by excessive consumption behavior and orientation to worldly pleasures have become a widespread social phenomenon in the modern era. From an Islamic perspective, this kind of behavior is contrary to the fundamental values that the Qur'an teaches, especially through the prohibition against al-isr?f (excess) and at-tabdz?r (extravagance). This study aims to analyze the phenomenon of hedonistic living through a thematic interpretation approach to the verses of the Qur'an, as well as relate it to the Islamic economic framework. The results of the study show that the Qur'an not only condemns individual consumptive behavior, but also warns of its impact on social structure, economic inequality, and loss of moral responsibility. The hedonistic lifestyle is also considered to be contrary to the principles of al-fal?h and maq??id al-shar?'ah which emphasize a balance between material and spiritual needs. Therefore, the value of simplicity and wise management of wealth is a Qur'anic solution in dealing with the crisis of excessive consumption and encouraging the realization of a fair and sustainable economic order.